The Influence Of Tax Planning, Deferred Tax Expenses, Managerial Proficiency, And Managerial Ownership On Earnings Management: (Case Study In The Food Sector Idx 2017-2021) - Aisyah Milafatma Noeraini; Ariyani (NAROTAMA UNIVERSITY, Indonesia, 2023)
This study aims to analyze the effect of tax planning, deferred tax expense, managerial skills, and managerial ownership on earnings management. This study uses a quantitative approach in the form of financial statements of food and beverage companies listed on the Indonesia Stock Exchange from 2017 to 2021. The sampling technique used in this study used a purposive sampling approach, the number of samples used in this study were 85 samples. The results of this study indicate that tax planning has an effect on earnings management, deferred tax expense has an effect on earnings management, managerial skills have no effect on earnings management, managerial ownership has no effect on earnings management and tax planning, deferred tax expenses, managerial skills and managerial ownership have an effect simultaneously on earnings management. The study uses only one dependent variable, namely earnings management, and uses 4 independent variables, namely Tax Planning, Deferred Tax Expenses, Managerial Skills and Managerial Ownership, this research does not use it until 2022 because the financial reports of the sample companies have not yet been published. For companies this research is used to add insight regarding the effect of tax planning, deferred tax expense and managerial skills and managerial ownership on earnings management. This Paper is Original.